CEO Information Ability, Absorptive Capacity, and E-Commerce Adoption among Small, Medium, and Micro Enterprises in China - Jiafeng Gu (Sustainability, 2022)
The purpose of this study was to explore the relationship between chief executive officer (CEO) characteristics, absorptive capacity, and e-commerce adoption in SMMEs. To achieve this objective, the study analyzed primary data gathered from 2675 small, medium, and micro enterprises (SMMEs) in China. A logistic regression model was employed to estimate how the CEO characteristics and absorptive capacity of SMMEs influenced their e-commerce adoption. The study revealed a significant positive relationship between CEO information ability, confidence, and e-commerce adoption. Additionally, this study confirmed a positive relationship between absorptive capacity and the adoption of e-commerce.